Design, synthesis and evaluation of the anti-breast cancer activity of 1, 3-oxazolo[4, 5-d]pyrimidine and 1, 3-oxazolo[5, 4-d]pyrimidine derivatives. Issue 4 (3rd March 2023) - Velihina, Yevheniia; Gesese, Raey; Zhirnov, Victor; Kobzar, Oleksandr; Bui, Benjamin; Pilyo, Stepan; Vovk, Andriy; Shen, Hai-Ying; Brovarets, Volodymyr
Abstract : The prepared oxazolopyrimidine derivatives exhibited high anti-breast-cancer activity and ADK suppression, indicating their potential as candidates in the targeted search for new, highly effective antitumor drugs. Abstract : A series of 1, 3-oxazolo[4, 5- d ]pyrimidine and 1, 3-oxazolo[5, 4- d ]pyrimidine derivatives were synthesized and functionalized in this study. The obtained compounds were tested against breast cancer cell lines of the NCI subpanel, followed by further analysis using the COMPARE algorithm from the Therapeutics Development Program, NCI. All synthesized derivatives displayed activity against most cell lines in the range of micromolar concentrations in terms of all parameters studied. Oxazolopyrimidine 5 exhibited the highest antitumor activity. A standard COMPARE analysis of the compounds showed that the vectors of the cytotoxic activity of derivatives 10 and 11 displayed a close to very high correlation with tamoxifen, and oxazolopyrimidine 13 displayed a very high correlation with the same drug. Five derivatives (2, 4, 6, 11 and 13 ) showed a high correlation with aclacinomycin A in the TGI vector. At the same time, compound 1 effectively suppressed ADK in cultured MDA-MB 231 cell lines, indicating that ADK is one of its targets through which it exerts anticancer properties. Based on molecular docking results, the possible binding mode of oxazolopyrimidine 1 to ADK has been suggested.